Do bilateral investment treaties attract foreign direct investment? The role of international dispute settlement provisions. (2nd December 2018) - Frenkel, Michael; Walter, Benedikt
Abstract: This paper studies the effects of the strength of bilateral investment treaties (BITs) on foreign direct investment (FDI) activity. We develop an index for the strength of international dispute settlement provisions included in BITs in order to examine the role the content of BITs plays in attracting FDI. To this end, we make use of data from UNCTAD's International Investment Agreement Mapping Project and measure the provision strength of 2, 571 BITs. Using panel data of bilateral and total FDI inflows and inward FDI stocks, we study the effect of BITs on FDI. Our main finding indicates that stronger international dispute settlement provisions in BITs are indeed associated with positive effects on FDI activity.